Exposure And Health Risk Assessment Of Aflatoxins In Hot Red Pepper Marketed In North Shewa Zone, Oromia Region, Ethiopia - Hundessa Alemu Degefe; Girma Salale Geleta (SAGE Publishing, 2024)
Aflatoxins (AFs) are secondary metabolites mainly produced by Aspergillus flavus and A. parasiticus and their contamination of red peppers can cause hepatocellular carcinoma, growth retardation in children, immune suppression, and death. In addition, their presence in the red peppers can affect international trade and cause significant economic burdens. Thus, the objective of this study was to assess the level of AFs contamination in packed powder (from supermarkets) and raw red pepper samples commercially available in the towns of Fiche and Mukaturi. Furthermore, this study aimed to determine the potential health and cancer risks associated with the consumption of red pepper contaminated with AFs. Red pepper samples (raw and packed powder) were collected randomly from the Fiche and Mukaturi open markets. Then AFs in the samples were extracted using methanol: water (80:20, v/v). These extract samples were then cleaned up using an immunoaffinity column (IAC) and determined with a high-performance liquid chromatography-fluorescence detector (HPLC-FLD). The finding showed that the amount of AFB 1 , AFB 2 , and AFG 1 in raw red pepper was found to be 3.19 ± 0.01, 0.19 ± 0.001, and 4.07 ± 0.01 μg kg −1 , respectively. The raw red pepper samples had a total of 7.66 ± 0.01 μg kg −1  of AFs. On the other hand, the amount of AFB 1 , AFB 2 , and AFG 1 in Afiya-packed red pepper was found to be 7.04 ± 0.03, 2.15 ± 0.06, and 0.50 ± 0.01 μg kg −1 , while Mudayi packed red pepper contained 31.60 ± 0.22, 24.40 ± 0.17, 3.37 ± 0.02 and 2.48 ± 0.004 μg kg −1  of aflatoxins, respectively. Afiya and Mudayi packed powder peppers had a total AFs content of 10.4 ± 0.07 and 61.90 ± 0.28 μg kg −1 , respectively. The total AFs concentrations in packed pepper powder samples were higher than maximum toleratable limits (MTLs) set by the European Commission Regulation (EU) 2023/915 (5.00 μg kg −1  for AFB 1 and 10 μg kg −1  for total AFs). AFB 1 (31.60 ± 0.22 μg kg −1 ) had the highest level of contamination, followed by AFB 2 (24.40 ± 0.17 μg kg −1 ) in packed pepper powder. In the adult population, the estimated daily intake (EDI) of AFB 1 , AFB 2 , AFG 1 , and AFG 2 ranged from 0.80 to 7.90, 0.04 to 6.10, 0.02 to 1.02, and 0.05 to 0.62  μ g kg −1 body weight (bw) per day, respectively. However, the Margins of Exposure (MOE) values and combined Margin of Exposure (MoET) for these chemicals were significantly lower than the safe margin (<10 000). Therefore, this study highlights the potential health risks associated with consuming AFs-contaminated red peppers and the need for stricter regulations and monitoring to ensure food safety.